A New Chromone from Stems of Cassia fistula and Its Anti-Tobacco Mosaic Virus Activities - Xia, Congfang; Yang, Yuchun; Meng, Yanlin; Qin, Ying; Hu, Qiufen; Ye, Yanqing (Asian Journal of Chemistry, 2014)
A new chromone, 5-hydroxy-2,2-dimethyl-7-(2-oxopropyl)-2,3-dihydrochromen-4-one (1) was isolated from the stems of Cassia fistula. Its structure was elucidated by spectroscopic methods, including extensive 1D- and 2D-NMR techniques. Compound 1 was evaluated for its anti-tobacco mosaic virus (anti-TMV) activity. The results showed that 1 exhibit potential anti-TMV activity with inhibition rate of 16.8 %.